1997
DOI: 10.1086/303467
|View full text |Cite
|
Sign up to set email alerts
|

MACHO Project Photometry of RR Lyrae Stars in the Sagittarius Dwarf Galaxy

Abstract: We report the discovery of 30 type a,b RR Lyrae (RRab) which are likely members of the Sagittarius (Sgr) dwarf galaxy. Accurate positions, periods, amplitudes and magnitudes are presented. Their distances are determined with respect to RRab in the Galactic bulge found also in the MACHO 1993 data. For R ⊙ = 8 kpc, the mean distance to these stars is D = 22 ± 1 kpc, smaller

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 28 publications
5
57
0
1
Order By: Relevance
“…From this Figure we conclude that their colors and reddening-independent magnitudes are consistent with bulge blue stragglers. This is confirmed also by the location of~Scuti stars (triangles) with respect to bulge RR Lyrae type ab (crosses, from Alcock et al 1997) in the color magnitude diagram shown in Figure 3b. use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0074180900116808 We assume that the line of sight distributions of d Scu and RR Lyrae stars are similar.…”
Section: The Evolutionary Status Of 6 Seu Stars In the Bulge Fieldssupporting
confidence: 67%
“…From this Figure we conclude that their colors and reddening-independent magnitudes are consistent with bulge blue stragglers. This is confirmed also by the location of~Scuti stars (triangles) with respect to bulge RR Lyrae type ab (crosses, from Alcock et al 1997) in the color magnitude diagram shown in Figure 3b. use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0074180900116808 We assume that the line of sight distributions of d Scu and RR Lyrae stars are similar.…”
Section: The Evolutionary Status Of 6 Seu Stars In the Bulge Fieldssupporting
confidence: 67%
“…Even taking into account that Sgr RR Lyrae stars are mixed with the Milky Way halo variables, some RR Lyrae stars found towards these coordinates have been associated with the dwarf galaxy by MACHO (Alard 1996;Alcock et al 1997) and OGLE (Soszyński et al 2014).…”
Section: Distances and The 3d View Of The Outer Bulgementioning
confidence: 99%
“…RR Lyrae stars are excellent distance indicators, as well as superb tracers of stellar substructures away from the Galactic plane (Mateo et al 1993;Alcock et al 1997). In order to pinpoint RR Lyrae star candidates within the 3FGL 95% uncertainty ellipses, we adopted a simple SDSS color cut scheme based on Equations (1)-(4) derived by Sesar et al (2010).…”
Section: Globular Clusters/dwarf Galaxies: Optical Searchmentioning
confidence: 99%